1995
DOI: 10.1209/0295-5075/29/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Escape Transitions and Force Laws for Compressed Polymer Mushrooms

Abstract: PACS. 36.20Ey -Macromolecules and polymer molecules: conformation (statistics and dynamics). PACS. 87.15 -v -Molecular biophysics. PACS. 46.30Lx -State buckling and instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 9 publications
3
78
1
Order By: Relevance
“…Theory and simulations showed that the polymer chains partially avoid compression by escaping from underneath the AFM tip [838][839][840][841]. This escaping of chains is not only effective in the mushroom regime [842] but also in the brush regime [843].…”
Section: Steric Forcesmentioning
confidence: 98%
“…Theory and simulations showed that the polymer chains partially avoid compression by escaping from underneath the AFM tip [838][839][840][841]. This escaping of chains is not only effective in the mushroom regime [842] but also in the brush regime [843].…”
Section: Steric Forcesmentioning
confidence: 98%
“…The goal of this paper is to present a rigorous analytical theory for a phase transition in a single macromolecule that has received much attention recently, namely the escape transition observed for an end-tethered chain compressed between two pistons [8][9][10][11][12][13][14][15][16][17][18]. At weak compressions, the chain is deformed uniformly to make a relatively thick pancake; the resistance force due to the compressed chain increases monotonously as the distance between two pistons, H, decreases.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium properties of the escape transition were investigated thoroughly by scaling theory [8,9], numerical calculations [10,15], and computer modeling [13,14,18]. The main result relates the critical compression distance H * to the piston radius, L, and the chain length, Na.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we can alternatively employ an approximate scaling approach or "blobology" instead of the Flory approach, as has been done in the simpler end-tethered squashing problem. 3,4 However the adoption of blobology would not change the qualitative results as can be demonstrated by redoing the end-tethered problem in Subramanian et al 3,4 using the Flory approach. We acknowledge that by using the size R of the nucleus as a minimization variable (rather than performing a functional minimization to find the density distribution which in turn provides R) we imprecisely predict the size of the nucleus, R. However, as long as the radius of the compressing cylinders is sufficiently large, i.e., we choose L > R, then the inarguable qualitative results will remain the same: compression will result in multiple escapes and with each partial escape of an arm, the nucleus will decrease with size.…”
mentioning
confidence: 99%